2022
DOI: 10.1111/ecc.13676
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and controversies patients and (health care) professionals experience in managing vaginal, vulvar, penile or anal cancer: The SILENCE study

Abstract: Objective: Patients with vaginal, vulvar, penile or anal cancer experience deteriorated psychosocial functioning and decreased Quality of Life (QoL). The aims of this study were to explore (1) the challenges and controversies patients experience in managing vaginal, vulvar, penile or anal cancer; their unmet needs; and how this affects their psychosocial functioning and (2) the gaps health care professionals (HCPs) experience in providing psychosocial support and potential improvements in care.Methods: Semi-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…The lack of dialogue strengthens taboos and the privatisation of the problem, leading to major negative consequences for the woman and her potential partner(s). Moreover, a study investigating rare cancers, including VC, described patients experiencing a 'double hit'; they received a cancer diagnosis and found that the location of the tumour hampered communication, especially regarding sexuality (van Dongen et al, 2022). The patients lacked psychosocial care, and the patients suggested that such care be delivered on a structural basis since referrals to psychologists or sexologists were insufficient (van Dongen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The lack of dialogue strengthens taboos and the privatisation of the problem, leading to major negative consequences for the woman and her potential partner(s). Moreover, a study investigating rare cancers, including VC, described patients experiencing a 'double hit'; they received a cancer diagnosis and found that the location of the tumour hampered communication, especially regarding sexuality (van Dongen et al, 2022). The patients lacked psychosocial care, and the patients suggested that such care be delivered on a structural basis since referrals to psychologists or sexologists were insufficient (van Dongen et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, the affected patients share common health inequities, leading to a significantly lower 5-year survival rate compared to common cancer types [7]. Similar to rare diseases [8], rare cancers are characterized by health discrimination [9], scarce information [10,11], limited research opportunities [12], lack of targeted preventive policies [13], difficulties in accurate diagnosis [14], and fragmented clinical management [15][16][17][18][19]. While these public health problems are evident at the member state level, it is also observed that Eastern European countries exhibit significantly lower 5-year survival rates for rare cancers compared to their Western European counterparts [6].…”
Section: Introduction 1backgroundmentioning
confidence: 99%